Primary breast tuberculosis - Filippou, Dimitrios C. (Radiology and oncology (Ljubljana), 2003)
Background. The differential diagnosis of primary breast tuberculosis with other benign or malignant conditions can be difficult with the current imagingtechniques that used to recognize breast pathologies. In many cases mammographic and ulfrasound characteristics of breast tuberculosis are similarto those of breast cancer, Case report. We present a case o f primary breast tuberculosis, with no previous history of the disease, which was diagnosed during the operation. Conclusions. Primary breast tuberculosis can be misdiagnosed. In these cases a tuberculosis infection history is negative, the mammographic and radiological findings obscure and the mass can be misdiagnosed as carcinoma. The diagnosis is achieved after the surgical removal of the mass and histological examination of the specimen,
Keywords: Aged; Antitubercular Agents; Antituberkulotiki; Biopsija igelna; Biopsy, Needle; breast; Diagnosis; diagnostika; dojke; Mammography; Mamografija; Mastitis; Starostniki; Therapy; Tuberculosis, Female Genital; tuberkuloza; Tuberkuloza genitalna, ženska; Ultrasonografija dojke; Ultrasonography, Mammary